# Deduction theorem

﻿
Deduction theorem

In mathematical logic, the deduction theorem is a metatheorem of first-order logic.[1] It is a formalization of the common proof technique in which an implication A → B is proved by assuming A and then proving B from this assumption. The deduction theorem explains why proofs of conditional sentences in mathematics are logically correct. Though it has seemed "obvious" to mathematicians literally for centuries that proving B from A conjoined with a set of theorems is sufficient to proving the implication A → B based on those theorems alone, it was left to Herbrand and Tarski to show (independently) this was logically correct in the general case—another instance, perhaps, of modern logic "cleaning up" mathematical practice.

The deduction theorem states that if a formula B is deducible from a set of assumptions $\Delta \cup \{A\}$, where A is a closed formula, then the implication A → B is deducible from $\Delta \,.$ In symbols, $\Delta \cup \{A\} \vdash B$ implies $\Delta \vdash A \to B \,.$. In the special case where $\Delta \,$ is the empty set, the deduction theorem shows that $A \vdash B$ implies $\vdash A \to B.$

The deduction theorem holds for all first-order theories with the usual deductive systems for first-order logic. However, there are first-order systems in which new inference rules are added for which the deduction theorem fails.[2]

The deduction rule is an important property of Hilbert-style systems because the use of this metatheorem leads to much shorter proofs than would be possible without it. Although the deduction theorem could be taken as primitive rule of inference in such systems, this approach is not generally followed; instead, the deduction theorem is obtained as an admissible rule using the other logical axioms and modus ponens. In other formal proof systems, the deduction theorem is sometimes taken as a primitive rule of inference. For example, in natural deduction, the deduction theorem is recast as an introduction rule for "→".

## Examples of deduction

"Prove" axiom 1:

• P 1. hypothesis
• Q 2. hypothesis
• P 3. reiteration of 1
• QP 4. deduction from 2 to 3
• P→(QP) 5. deduction from 1 to 4 QED

"Prove" axiom 2:

• P→(QR) 1. hypothesis
• PQ 2. hypothesis
• P 3. hypothesis
• Q 4. modus ponens 3,2
• QR 5. modus ponens 3,1
• R 6. modus ponens 4,5
• PR 7. deduction from 3 to 6
• (PQ)→(PR) 8. deduction from 2 to 7
• (P→(QR))→((PQ)→(PR)) 9. deduction from 1 to 8 QED

Using axiom 1 to show ((P→(QP))→R)→R:

• (P→(QP))→R 1. hypothesis
• P→(QP) 2. axiom 1
• R 3. modus ponens 2,1
• ((P→(QP))→R)→R 4. deduction from 1 to 3 QED

## Virtual rules of inference

From the examples, you can see that we have added three virtual (or extra and temporary) rules of inference to our normal axiomatic logic. These are "hypothesis", "reiteration", and "deduction". The normal rules of inference (i.e. "modus ponens" and the various axioms) remain available.

1. Hypothesis is a step where one adds an additional premise to those already available. So, if your previous step S was deduced as:

$E_1, E_2, ... , E_{n-1}, E_n \vdash S,$

then one adds another premise H and gets:

$E_1, E_2, ... , E_{n-1}, E_n, H \vdash H.$

This is symbolized by moving from the n-th level of indentation to the n+1-th level and saying

• S previous step
• H hypothesis

2. Reiteration is a step where one re-uses a previous step. In practice, this is only necessary when one wants to take a hypothesis which is not the most recent hypothesis and use it as the final step before a deduction step.

3. Deduction is a step where one removes the most recent hypothesis (still available) and prefixes it to the previous step. This is shown by unindenting one level as follows:

• H hypothesis
• ......... (other steps)
• C (conclusion drawn from H)
• HC deduction

## Conversion from proof using the deduction meta-theorem to axiomatic proof

In axiomatic versions of propositional logic, one usually has among the axiom schemas (where P, Q, and R are replaced by any propositions):

• Axiom 1 is: P→(QP)
• Axiom 2 is: (P→(QR))→((PQ)→(PR))
• Modus ponens is: from P and PQ infer Q

These axiom schemas are chosen to enable one to derive the deduction theorem from them easily. So it might seem that we are begging the question. However, they can be justified by checking that they are tautologies using truth tables and that modus ponens preserves truth.

From these axiom schemas one can quickly deduce the theorem schema PP (reflexivity of implication) which is used below:

1. (P→((QP)→P))→((P→(QP))→(PP)) from axiom schema 2 with P, (QP), P
2. P→((QP)→P) from axiom schema 1 with P, (QP)
3. (P→(QP))→(PP) from modus ponens applied to step 2 and step 1
4. P→(QP) from axiom schema 1 with P, Q
5. PP from modus ponens applied to step 4 and step 3

Suppose that we have that Γ and H prove C, and we wish to show that Γ proves HC. For each step S in the deduction which is a premise in Γ (a reiteration step) or an axiom, we can apply modus ponens to the axiom 1, S→(HS), to get HS. If the step is H itself (a hypothesis step), we apply the theorem schema to get HH. If the step is the result of applying modus ponens to A and AS, we first make sure that these have been converted to HA and H→(AS) and then we take the axiom 2, (H→(AS))→((HA)→(HS)), and apply modus ponens to get (HA)→(HS) and then again to get HS. At the end of the proof we will have HC as required, except that now it only depends on Γ, not on H. So the deduction step will disappear, consolidated into the previous step which was the conclusion derived from H.

To minimize the complexity of the resulting proof, some preprocessing should be done before the conversion. Any steps (other than the conclusion) which do not actually depend on H should be moved up before the hypothesis step and unindented one level. And any other unnecessary steps (which are not used to get the conclusion or can be bypassed), such as reiterations which are not the conclusion, should be eliminated.

During the conversion, it may be useful to put all the applications of modus ponens to axiom 1 at the beginning of the deduction (right after the HH step).

When converting a modus ponens, if A is outside the scope of H, then it will be necessary to apply axiom 1, A→(HA), and modus ponens to get HA. Similarly, if AS is outside the scope of H, apply axiom 1, (AS)→(H→(AS)), and modus ponens to get H→(AS). It should not be necessary to do both of these, unless the modus ponens step is the conclusion, because if both are outside the scope, then the modus ponens should have been moved up before H and thus be outside the scope also.

Under the Curry–Howard correspondence, the above conversion process for the deduction meta-theorem is analogous to the conversion process from lambda calculus terms to terms of combinatory logic, where axiom 1 corresponds to the K combinator, and axiom 2 corresponds to the S combinator. Note that the I combinator corresponds to the theorem schema PP.

## The deduction theorem in predicate logic

The deduction theorem is also valid in first-order logic in the following form:

• If T is a theory and F, G are formulas with F closed, and T∪{F}├G, then TFG.

Here, the symbol ├ means "is a syntactical consequence of." We indicate below how the proof of this deduction theorem differs from that of the deduction theorem in propositional calculus.

In the most common versions of the notion of formal proof, there are, in addition to the axiom schemes of propositional calculus (or the understanding that all tautologies of propositional calculus are to be taken as axiom schemes in their own right), quantifier axioms, and in addition to modus ponens, one additional rule of inference, known as the rule of generalization: "From K, infer ∀vK."

In order to convert a proof of G from T∪{F} to one of FG from T, one deals with steps of the proof of G which are axioms or result from application of modus ponens in the same way as for proofs in propositional logic. Steps which result from application of the rule of generalization are dealt with via the following quantifier axiom (valid whenever the variable v is not free in formula H):

• (HK)→(H→∀vK).

Since in our case F is assumed to be closed, we can take H to be F. This axiom allows one to deduce F→∀vK from FK, which is just what is needed whenever the rule of generalization is applied to some K in the proof of G.

## Example of conversion

To illustrate how one can convert a natural deduction to the axiomatic form of proof, we apply it to the tautology Q→((QR)→R). In practice, it is usually enough to know that we could do this. We normally use the natural-deductive form in place of the much longer axiomatic proof.

First, we write a proof using a natural-deduction like method:

• Q 1. hypothesis
• QR 2. hypothesis
• R 3. modus ponens 1,2
• (QR)→R 4. deduction from 2 to 3
• Q→((QR)→R) 5. deduction from 1 to 4 QED

Second, we convert the inner deduction to an axiomatic proof:

• (QR)→(QR) 1. theorem schema (AA)
• ((QR)→(QR))→(((QR)→Q)→((QR)→R)) 2. axiom 2
• ((QR)→Q)→((QR)→R) 3. modus ponens 1,2
• Q→((QR)→Q) 4. axiom 1
• Q 5. hypothesis
• (QR)→Q 6. modus ponens 5,4
• (QR)→R 7. modus ponens 6,3
• Q→((QR)→R) 8. deduction from 5 to 7 QED

Third, we convert the outer deduction to an axiomatic proof:

• (QR)→(QR) 1. theorem schema (AA)
• ((QR)→(QR))→(((QR)→Q)→((QR)→R)) 2. axiom 2
• ((QR)→Q)→((QR)→R) 3. modus ponens 1,2
• Q→((QR)→Q) 4. axiom 1
• [((QR)→Q)→((QR)→R)]→[Q→(((QR)→Q)→((QR)→R))] 5. axiom 1
• Q→(((QR)→Q)→((QR)→R)) 6. modus ponens 3,5
• [Q→(((QR)→Q)→((QR)→R))]→([Q→((QR)→Q)]→[Q→((QR)→R))]) 7. axiom 2
• [Q→((QR)→Q)]→[Q→((QR)→R))] 8. modus ponens 6,7
• Q→((QR)→R)) 9. modus ponens 4,8 QED

These three steps can be stated succinctly using the Curry–Howard correspondence:

• first, in lambda calculus, the function f = λa. λb. b a has type q → (qr) → r
• second, by lambda elimination on b, f = λa. s i (k a)
• third, by lambda elimination on a, f = s (k (s i)) k

## Paraconsistent deduction theorem

In general, the classical deduction theorem doesn't hold in paraconsistent logic. However, the following "two-way deduction theorem" does hold in one form of paraconsistent logic:[3]

$\vdash E \rightarrow F$ if and only if ($E \vdash F$ and $\neg F \vdash \neg E$)

that requires the contrapositive inference to hold in addition to the requirement of the classical deduction theorem.

## The resolution theorem

The resolution theorem is the converse of the deduction theorem. It follows immediately from modus ponens which is the elimination rule for implication.

## Notes

1. ^ Kleene 1967, p. 39, 112; Shoenfield 1967, p. 33
2. ^ Kohlenbach 2008, p. 148
3. ^ Hewitt 2008

## References

• Carl Hewitt (2008), "ORGs for Scalable, Robust, Privacy-Friendly Client Cloud Computing", IEEE Internet Computing 12 (5): 96, doi:10.1109/MIC.2008.107.  September/October 2008
• Kohlenbach, Ulrich (2008), Applied proof theory: proof interpretations and their use in mathematics, Springer Monographs in Mathematics, Berlin, New York: Springer-Verlag, ISBN 978-3-540-77532-4, MR2445721
• Kleene, Stephen Cole (2002) [1967], Mathematical logic, New York: Dover Publications, ISBN 978-0-486-42533-7, MR1950307
• Shoenfield, Joseph R. (2001) [1967], Mathematical Logic (2nd ed.), A K Peters, ISBN 978-1-56881-135-2

Wikimedia Foundation. 2010.

### Look at other dictionaries:

• deduction theorem — The theorem provable about some logical systems, that if a conclusion C can be proved from a set of premises A1…An, then there is a proof of An→ C from A1…An–1 …   Philosophy dictionary

• theorem — [n] explanation based on hypothesis and experiments assumption, axiom, belief, deduction, dictum, doctrine, formula, fundamental, law, postulate, principium, principle, proposition, rule, statement, theory, thesis; concepts 529,688,689 Ant. fact …   New thesaurus

• Theorem — The Pythagorean theorem has at least 370 known proofs[1] In mathematics, a theorem is a statement that has been proven on the basis of previously established statements, such as other theorems, and previously accepted statements …   Wikipedia

• theorem — Synonyms and related words: a priori principle, a priori truth, affirmation, apriorism, assertion, assumed position, assumption, axiom, basis, brocard, categorical proposition, conjecture, data, deduction, dictate, dictum, first principles,… …   Moby Thesaurus

• Hilbert-style deduction system — In logic, especially mathematical logic, a Hilbert style deduction system is a type of system of formal deduction attributed to Gottlob FregeMáté Ruzsa 1997:129] and David Hilbert. These deductive systems are most often studied for first order… …   Wikipedia

• Natural deduction — In logic and proof theory, natural deduction is a kind of proof calculus in which logical reasoning is expressed by inference rules closely related to the natural way of reasoning. This contrasts with the axiomatic systems which instead use… …   Wikipedia

• Gödel's completeness theorem — is a fundamental theorem in mathematical logic that establishes a correspondence between semantic truth and syntactic provability in first order logic. It was first proved by Kurt Gödel in 1929. A first order formula is called logically valid if… …   Wikipedia

• Proof sketch for Gödel's first incompleteness theorem — This article gives a sketch of a proof of Gödel s first incompleteness theorem. This theorem applies to any formal theory that satisfies certain technical hypotheses which are discussed as needed during the sketch. We will assume for the… …   Wikipedia

• Löwenheim–Skolem theorem — In mathematical logic, the Löwenheim–Skolem theorem, named for Leopold Löwenheim and Thoralf Skolem, states that if a countable first order theory has an infinite model, then for every infinite cardinal number κ it has a model of size κ. The… …   Wikipedia

• Automated theorem proving — (ATP) or automated deduction, currently the most well developed subfield of automated reasoning (AR), is the proving of mathematical theorems by a computer program. Decidability of the problem Depending on the underlying logic, the problem of… …   Wikipedia